A steroid hormone agonist reduces female fitness in insecticide-resistant Anopheles populations - Brown, Faye; Paton, Douglas G.; Catteruccia, Flaminia; Ranson, Hilary; Ingham, Victoria A. (Insect biochemistry and molecular biology, 2020)
Insecticide based vector control tools such as insecticide treated bednets and indoor residual spraying represent the cornerstones of malaria control programs. Resistance to chemistries used in these programs is now widespread and represents a significant threat to the gains seen in reducing malaria-related morbidity and mortality. Recently, disruption of the 20-hydroxyecdysone steroid hormone pathway was shown to reduce Plasmodium development and significantly reduce both longevity and egg production in a laboratory susceptible Anopheles gambiae population. Here, we demonstrate that disruption of this pathway by application of the dibenzoylhydrazine, methoxyfenozide (DBH-M), to insecticide resistant An. coluzzii, An. gambiae sl and An. funestus populations significantly reduces egg production in both topical and tarsal application. Moreover, DBH-M reduces adult longevity when applied topically, and tarsally after blood feeding. As the cytochrome p450s elevated in pyrethroid resistant Anopheles only bind DBH-M very weakly, this compound is unlikely to be subject to cross-resistance in a field-based setting. Manipulation of this hormonal signalling pathway therefore represents a potential complementary approach to current malaria control strategies, particularly in areas where high levels of insecticide resistance are compromising existing tools. [Display omitted] •Topical application of methoxyfenozide is effective at sterilising insecticide resistant populations of African Anophelines.•Topical application also significantly decreases lifespan.•Tarsal application with the adjuvant RME similarly sterilises and shortens life span post-blood feeding.•Cytochrome p450s, major insecticide metabolisers, don’t show affinity for methoxyfenozide indicating no cross-resistance.•Methoxyfenozide has potential importance in a field-setting as a complementary vector control tool.